Many physiotherapists lack preparedness to prescribe physical activity and exercise to people with musculoskeletal pain: A multi-national survey. (May 2021) - Barton, C.J.; King, M.G.; Dascombe, B.; Taylor, N.F.; de Oliveira Silva, D.; Holden, S.; Goff, A.J.; Takarangi, K.; Shields, N.
Abstract: Objectives: Determine physiotherapists' (i) awareness of physical activity, and exercise prescription guidelines; (ii) perceived role, knowledge, confidence, skills and training in prescribing and progressing aerobic exercise and resistance training to people with musculoskeletal pain; (iii) professional development preferences; and (iv) perceived influences of external factors on exercise prescription for people with musculoskeletal pain. Design: Multi-national cross-sectional survey. Methods: An open online survey was developed specifically for this study. Results: 1, 352 physiotherapists from 56 countries participated. The majority of respondents correctly stated physical activity guidelines for adults (60%) and children (53%), but only 37% correctly stated guidelines for older adults. Eleven percent and 16% could name an accepted guideline for aerobic exercise and resistance training, respectively. Most agreed their role included prescribing aerobic exercise (75%) and resistance training (89%). Fewer reported they had the confidence, training or skills to prescribe aerobic exercise (38–50%) and resistance training (49–70%). Workshops were the most preferred (44%) professional development option. Most respondents believed appointment scheduling and access to equipment and professional development (62–79%) affected their ability to prescribe effective exercise. Conclusion: Many physiotherapists lack knowledge and training to provide physical activity advice, and to prescribe aerobic exercise and resistance training to people with musculoskeletal pain. Highlights: Most (75-89%) physiotherapists agreed their role involves aerobic exercise and resistance training prescription. Fewer reported they had the confidence, training, or skills to prescribe aerobic exercise and resistance training (38-67%). Physical activity guidelines for adults and children were correctly stated by 60% and 53% of respondents, respectively. Very few respondents were able to name an accepted guideline for aerobic exercise (11%) and resistance training (21%). Most respondents (79%) believed opportunity for professional development affected their ability to prescribe exercise.